2005
DOI: 10.1007/s00420-005-0066-3
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA damage correlates with polycyclic aromatic hydrocarbons biomarker in coke-oven workers

Abstract: A potential risk of sperm dysfunction should be considered for workers occupationally exposed to high levels of PAHs. Cigarette smoking may aggravate this risk. Urinary 1-OHP can be used as a biomarker predicting sperm dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 45 publications
6
34
2
1
Order By: Relevance
“…Although 1-OHP is the most commonly used indicator of PAHs exposure in many previously reported studies, some studies suggest that it may not represent the numerous PAHs metabolites [22]. However, in the study by Hsu et al (2006) [28] assessing the sperm damage after exposure to polycyclic aromatic hydrocarbons the authors noticed that 1-OHP can be used as a biomarker predicting sperm dysfunction [28]. Most of the studies which examine the association between exposure to PAHs and sperm quality indicate that 1-OHP may affect male semen quality even at non-occupational exposure levels [24,25,27,41].…”
Section: Ijomeh 2013;26(5) 797mentioning
confidence: 94%
See 2 more Smart Citations
“…Although 1-OHP is the most commonly used indicator of PAHs exposure in many previously reported studies, some studies suggest that it may not represent the numerous PAHs metabolites [22]. However, in the study by Hsu et al (2006) [28] assessing the sperm damage after exposure to polycyclic aromatic hydrocarbons the authors noticed that 1-OHP can be used as a biomarker predicting sperm dysfunction [28]. Most of the studies which examine the association between exposure to PAHs and sperm quality indicate that 1-OHP may affect male semen quality even at non-occupational exposure levels [24,25,27,41].…”
Section: Ijomeh 2013;26(5) 797mentioning
confidence: 94%
“…One cohort study from Selevan et al (2000), [24] reports an association between air pollution episodes of elevated PAHs and the increased asthenospermia, abnormal morphology, and abnormal chromatin in human sperm. In the study by Hsu et al (2006) [28] among coke-oven workers from a steel plant in southern Taiwan occupationally exposed to high levels of PAHs, the number of workers with oligospermia and the percentage of abnormal sperm morphology was significantly greater in topside oven workers than in the side-oven workers. [28].…”
Section: Ijomeh 2013;26(5) 797mentioning
confidence: 94%
See 1 more Smart Citation
“…[37][38][39] Among xenoestrogens, phthalates are ubiquitous in human life. Hsu et al 40 and Han et al 41 reported that polycyclic aromatic hydrocarbons are associated with DNA damages. Recent studies have demonstrated that not only androgens but also oestrogens have an important role in male reproduction.…”
Section: Contribution Of Environmental Factorsmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are common toxic compounds generated from coal combustion during steel processing. Several PAH compounds have been reported to impair the reproductive capacity of males, including decreased semen quality in terms of concentration, motility and vitality [1][2][3]. Cellular deoxyribonucleic acid (DNA) has been suggested as a target in the subjects exposed to PAHs.…”
Section: Introductionmentioning
confidence: 99%